PSIKOLOGI PENDIDIKAN ISLAM: INTEGRASI TEORI PSIKOLOGIS DAN NILAI SPIRITUAL DALAM PEMBELAJARAN - Dipalpa Rego; Afnibar; Ulfatmi (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2025)
This study explores educational psychology from an Islamic perspective, emphasizing the importance of integrating modern psychological theories with spiritual values. The background of this research is rooted in the transformation of 21st-century education, characterized by globalization, digitalization, and student diversity. The main issues discussed involve understanding the concepts of psychology, education, learning, and instruction, as well as their relevance to Islamic educational principles. The study applies a literature review method by analyzing key theories in educational psychology, particularly cognition, motivation, and development, and then linking them with Islamic perspectives. The findings indicate that educational psychology plays a significant role in designing curricula, instructional strategies, and effective assessment systems. Meanwhile, Islamic education views learning as an act of worship that integrates faith, knowledge, and practice to form the ideal human being (insan kamil). The integration of these two perspectives leads to a learning model that not only emphasizes cognitive intelligence but also strengthens moral character, spirituality, and students’ social contributions. Thus, this synthesis offers a more holistic and meaningful educational framework..